2013
DOI: 10.4028/www.scientific.net/kem.543.200
|View full text |Cite
|
Sign up to set email alerts
|

Biosafety Evaluation of Nanoparticles in View of Genotoxicity and Carcinogenicity Studies: A Systematic Review

Abstract: Nanoparticles (NPs) are used in various forms in consumer products including, cosmetics, food packaging, textiles and also in air and water cleaning, production of electro chromic windows, or smart windows and gas sensors. Many NPs have also been evaluated for potential use in biomedical applications as efficient delivery carriers for cancer diagnosis and therapy. Nowadays, NPs are being developed to create fascinating nanotechnology products. To develop NPs for broad applications, potential risks to human hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2013
2013
2014
2014

Publication Types

Select...
4

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Thus, studying the toxicity of nanomaterials is of importance to provide guidance to occupational health and safety (Li et al, 2008;Liu et al, 2011). The discussion about safety concerns associated with small particles is ongoing for many decades and is largely related to potential risks following inhalative exposure (e.g., Gao et al, 2013;Schmid et al, 2009;Turkez et al, 2013a;Wang et al, 2013). In particular, ultrafine particles or NPs are the focus of the debate (e.g., ECETOC, 2006;Singh et al, 2013), and usually meant to have one or more size dimensions between 0.1 and 100 nm (Hasegawa et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, studying the toxicity of nanomaterials is of importance to provide guidance to occupational health and safety (Li et al, 2008;Liu et al, 2011). The discussion about safety concerns associated with small particles is ongoing for many decades and is largely related to potential risks following inhalative exposure (e.g., Gao et al, 2013;Schmid et al, 2009;Turkez et al, 2013a;Wang et al, 2013). In particular, ultrafine particles or NPs are the focus of the debate (e.g., ECETOC, 2006;Singh et al, 2013), and usually meant to have one or more size dimensions between 0.1 and 100 nm (Hasegawa et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…But the toxic effects of nano sized particles have not fully studied, except for some inorganic and organic NPs. In fact, a recent report indicated that there was a lack of systematic assessment of the DNA damaging and carcinogenic potential of NPs in spite of their extensive use in nanotechnological applications (Turkez et al 2013b). Tungsten (VI) oxide (or tungsten trioxide: WO 3 ) is a chemical compound containing oxygen and the transition metal tungsten.…”
Section: Introductionmentioning
confidence: 99%
“…But the toxic effects of nano-sized particles were not fully detailed except for some titanium, tungsten, cadmium and zinc oxide nanoparticles (Zhang et al 2013). However, the recent report indicated that there was a lack of systematic assessment of the DNA damaging and carcinogenic potential of NPs in spite of their extensive use in nanotechnological applications (Turkez et al 2013b).…”
Section: Introductionmentioning
confidence: 99%